Analisis Strategi Promosi untuk Meluncurkan New Product Development pada Brand Pikopi (Studi Kasus di PT Santos Jaya Abadi) (Journal of Entrepreneurship, Management and Industry (JEMI), 2023)
PT Santos Jaya Abadi experienced a decrease in volume share from 2020 to 2021, due to a decrease in the sales volume of established brands that position themselves as high quality ground coffee products at higher prices. The PIKOPI brand is the newest brand that acts as a fighting brand with low end entry level product segmentation to compete with direct competitors with the aim of increasing SJA's competitive price and volume share in 2022. This study aims to determine Segmentation, Targeting, and Positioning, Marketing 4P's mix, and promotional strategies implemented for the Launch of New Products on the PIKOPI Brand to increase the company's volume share. The research method uses a qualitative approach with a single explorative case study. The promotion strategy carried out by PIKOPI by implementing 360 degree integrated marketing communications through Above The Line, Below The Line Activity, and Online Activity activities at each stage of the customer experience journey with several stages that must be passed, namely: discovery experience, purchasing experience, successful usage experience supports PIKOPI's performance to increase consumer appeal, so that SJA's volume share increases in 2022.